Studies of the Adsorption of Organic Vapours by Metal Stearates and Their Complexes with Octadecylamine in a Flow Impulse Regime by Piezoquartz Sensor Techniques - Aleksei P. Filippov; Peter E. Strizhak; Tamila G. Serebry (Adsorption Science & Technology)
The adsorption properties of metal (Co 2+ , Ni 2+ and Cu 2+ ) stearates and their coordination compounds with octadecylamine, as well as those of carbon nanotubes (CNTs), have been studied by piezoquartz resonator (PQR) sensor techniques in steady flow and flow impulse regimes for vapours of volatile organic compounds (VOCs), especially hydrocarbons. It was shown that the adsorption of hydrocarbon homologues onto each of the studied sensor coverings was characterized by a linear dependence between the logarithm of the Henry constant and the boiling points of the corresponding substances. Such individual linear dependencies were observed for a series of alkanes, cyclanes and aromatics. The slopes of these dependencies differed for different sensor coverings. This allowed discrimination between individual hydrocarbon analogues by using these coverings in a PQR sensor array in combination with the proposed flow impulse technique.